Models of Research and Development Financing in the European Union: A Cluster Analysis - Stefanova, Kristina (Research Papers, 2021)
The paper aims to identify the different models of financing the expenditure on research and development in the European Union and define their characteristics through the application of the method of cluster analysis. The study shows the existence of four models within the EU, which are characterised by different ratios of R&D funding sources and have a specific geographical profile. Despite the differences, the private or public sector is defined as the funding source with the largest relative share in all models. The analysis shows that the model with the highest share of private sector funding provides the highest R&D expenditure as a percentage of GDP.
Keywords: Research and development; Financing R&D; Innovations; European union; Cluster analysis